De novo assembly of transcriptome during regeneration post-arm amputation in the starfish, Asterias amurensis - Mi Jeong Jo; Hye-Jin Go; Jeong Gyu Kim; Gun-Do Kim (BMC Genomic Data)
Abstract Objectives This study investigates the nerve cord transcriptome of Asterias amurensis to explore its regenerative abilities. By comparing gene expression between a normal group and a group 72 h post-amputation, key genes involved in regeneration were identified. Functional annotation using GO, KEGG, NR, and UniProt databases provided insights into the biological roles of these genes. This research enhances the understanding of A. amurensis regeneration and highlights the need for further transcriptome analysis across different tissues. Data description A. amurensis, a starfish species found in the northwestern Pacific, is known for its strong predatory behavior and impact on marine biodiversity. In this study, individuals were divided into a normal group and a 72-hour post-amputation group. De novo transcriptome assembly of the nerve cord identified 257,769 unigenes, which were functionally annotated using GO, KEGG, NR, and UniProt databases. Since only nerve cord tissue was analyzed, additional transcriptome studies on various tissues are required for a more comprehensive understanding of A. amurensis biology.